The Relationship Between Organizational Citizenship Behaviours and Value Preferences of Teachers and Principals - EKŞİ, HALİL (My University, 2009)
The main purpose of this research is to investigate the relationship between organizational citizenship behaviours and value preferences of teachers and principals. The participants of this research includes 252 principals and teachers who are on duty in state schools in west side of Istanbul province. In addition, in the research personal information form, Schwartz value scale and Yücel organizational citizenship behaviours scale are used for collecting data. As result of the analyses, there is a meaningful relationship between the value preferences the organizational citizenship behaviours. As the importance given to the organizational citizenship behaviours increases, also the organizational citizenship behaviour increases. Keywords: Principals, teacher behavior, values, standard of value, organizational citizenship behaviour.

Bu araştırmayla yönetici ve öğretmenlerin değer tercihleri ile örgütsel vatandaşlık davranışı arasındaki ilişkinin ortaya çıkarılması amaçlanmıştır. Araştırmanın evrenini İstanbul ili Avrupa Yakası’ndaki resmî ortaöğretim kurumlarında görev yapan 252 yönetici ve öğretmenden oluşmaktadır. Ayrıca bu araştırmada; demografi k değişkenlerin toplanmasına yönelik kişisel bilgi formu, Schwartz Değerler Ölçeği ve Yücel Örgütsel Vatandaşlık Davranışı Ölçeği yer almaktadır. Yönetici ve öğretmenlerin değer tercihleri, demografi k özellikleri ile örgütsel vatandaşlık davranışı arasındaki ilişkinin var olduğu bu araştırmanın sonuçlarıyla ortaya konmuştur. Yönetici ve öğretmenlerin değer tercihleri ile örgütsel vatandaşlık davranışı arasında anlamlı bir ilişki vardır. Anahtar Kelimeler: Yöneticiler, öğretmen davranışı, değerler, değer ölçüleri, örgütsel vatandaşlık davranışı.
Yönetici ve Öğretmenlerin Değer Tercihleri ile Örgütsel Vatandaşlık Davranışları Arasındaki İlişki
Keywords: Sosyal ve Beşeri Bilimler; İşletme; Social Sciences and Humanities; Management; İŞLETME; Ekonomi ve İş; Sosyal Bilimler (SOC); BUSINESS; ECONOMICS & BUSINESS; Social Sciences (SOC); Strategy and Management; General Business, Management and Accounting; Business and International Management; Marketing; Social Sciences & Humanities; Principals; teacher behavior; values; standard of value; organizational citizenship behaviour; Yöneticiler; öğretmen davranışı; değerler; değer ölçüleri; örgütsel vatandaşlık davranışı